La imatge aristotèlica del paralític i la malaltia de la voluntat al poema 74 d'Ausiàs March. - ALMENAR, SALVADOR CUENCA I. (Scripta, 2016)
The paralysis metaphor is crucial to the understanding of the second stanza of March's poem 74. Two 13th century works, essential for the dissemination of Aristotle's thought, namely, the Summa Alexandrinorum and Aquinas's Sententia libri Ethicorum, use the metaphor to adress the same moral issue: the akrasia or weakness of the will. This paper will examine the relationship between poem 74 and those two Aristotelian works.